SARS-CoV-2 Causes Acute Kidney Injury by Directly Infecting Renal Tubules - Chen, Zhaohui (Front Cell Dev Biol, 2021)
Acute kidney injury (AKI) is one of the most prevalent complications among hospitalized coronavirus disease 2019 (COVID-19) patients. Here, we aim to investigate the causes, risk factors, and outcomes of AKI in COVID-19 patients. We found that angiotensin-converting enzyme II (ACE2) and transmembrane protease serine 2 (TMPRSS2) were mainly expressed by different cell types in the human kidney. However, in autopsy kidney samples, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleoprotein was detected in ACE2(+) or TMPRSS2(+) renal tubular cells, whereas the RNAscope(®) Assay targeting the SARS-CoV-2 Spike gene was positive mainly in the distal tubular cells and seldom in the proximal tubular cells. In addition, the TMPRSS2 and kidney injury marker protein levels were significantly higher in the SARS-CoV-2-infected renal distal tubular cells, indicating that SARS-CoV-2-mediated AKI mainly occurred in the renal distal tubular cells. Subsequently, a cohort analysis of 722 patients with COVID-19 demonstrated that AKI was significantly related to more serious disease stages and poor prognosis of COVID-19 patients. The progressive increase of blood urea nitrogen (BUN) level during the course of COVID-19 suggests that the patient’s condition is aggravated. These results will greatly increase the current understanding of SARS-CoV-2 infection.